PTU-020 High levels of "presumed polyp miss rate" at 1 and 3 years following index screening colonoscopy: no room for complacency. (17th June 2017) - Rameshshanker, R; Purchiaroni, F; Ana, W; Thomas-Gibson, S; Rajendran, A; Stasinos, I; Tsiamoulos, Z; Saunders, BP
Abstract : Introduction: Despite improvements in colonoscopy training and technology, it remains as an imperfect tool and the adenoma miss rates (AMR) vary between 6%–27%. Aim is to determine the presumed AMR and sessile serrated adenomas/polyps (SSA/Ps) miss rate after a complete screening colonoscopy. Method: It is a single centre prospective observational study over 12 months from July 2015. Patients who underwent 1 and 3 year screening surveillance colonoscopy performed by accredited screening colonoscopists were included. Polyp characteristics and procedural data were prospectively collected. Polyp histology and epidemiology data were retrieved from our endoscopy database. A polyp was considered as "missed" at the index colonoscopy if at 1 year surveillance or at 3 years if >5 mm, and not a recurrence. Results: 241 patients underwent a surveillance colonoscopy (male: female 2:1, median age 65 years). 90/241 (37.3%) patients had a one year surveillance colonoscopy. There was no significant difference in the quality of bowel preparation and caecal intubation rate between index and surveillance procedures. Total number of polyps detected during index and surveillance colonoscopies were 815 and 469 respectively. The presumed miss rate of polyps, adenomas, SSA/Ps and advanced adenomas were 37.8% (469/1241), 22.1% (176/798), 41.7% (20/48) and 15.2% (36/236) respectively. More adenomas were missed in the proximal colon (Image 1- missed adenoma and SSA/P in each segment) when compared to distal colon (26.64% vs 18.04%, p=0.01). Adenoma miss rates per size were 23.7%, 27.1% and 8.3% for diminutive, small and adenoma >1 cm respectively.Higher number of polyps (>3) detected during index colonoscopy independently correlated with high miss rates (84.3% vs 72%, p=0.04). Conclusion: Our study highlights that there is a significant miss rate for adenomas and SSA/Ps even after careful index colonoscopy. Miss rate was higher when multiple polyps are seen at the index examination. This finding appears to justify the current BSG guidelines for one year colonoscopy when multiple polyps are seen. The presumed polyp miss rate at 1 and 3 years may be justified as a new quality metric. Disclosure of Interest: None Declared